Incidental capture of sea turtles by longlines in the Gulf of Gabès (South Tunisia): A comparative study between bottom and surface longlines - Imed Jribi (Scientia Marina, 2008)
Longlines are a fishing gear that have traditionally been used world-wide. Surface longlines are mainly used to fish swordfish, albacore, tuna and some species of sharks, while bottom longlines are used to fish large bottom-dwelling fish such as groupers. Longlines are widely known to interact with several species of sea turtles, and there is increasing concern about the impact of by-catch on these species. However, there is a paucity of data on sea turtle interactions with bottom longlines. In this paper we analyse the interaction of sea turtles with both bottom and surface longlines in the zone of Zarzis in the south of the gulf of Gabès, which is considered to be an important Mediterranean wintering and foraging area for the loggerhead turtle, Caretta caretta. Results show an important interaction with both types of longlines. Catch rates were estimated to be 0.823 per 1000 hooks for surface longline and 0.278 per 1000 hooks for bottom longline. Direct mortalities were estimated to be 0% (n=33 captures) and 12.5% (n=24 captures), respectively.